Fiqh of Usrah and Aqidah Education as the Basis for the Moral Resilience of the Ummah - Haswira Salleh Ahim (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
The decline in morals among Muslims now shows an important need to reassess the role of Aqidah Education in family institutions. Although moral issues are often discussed from a social and psychological perspective, the teachings of Aqidah as the main guide to moral development are still not given due emphasis. Therefore, the objective of this study is to analyze the importance of Aqidah Education as a guide to moral development of individuals and families according to an Islamic perspective. This study uses a qualitative approach through document analysis or book study by examining primary and secondary sources such as the Quran, Hadith, books of turaths, contemporary works in the field of Aqidah and fiqh usrah and several academic articles. The results of the study found that Aqidah Education based on monotheism plays a fundamental role in forming strong, consistent and resilient morals, in addition to being the main bulwark in facing the influence of thoughts and lifestyles that contradict Islamic values. Finally, it also emphasizes the importance of strengthening Aqidah Education in the family to ensure the resilience of Muslim morals as a whole.